The Structure of CaSO4 Nanorods: The Precursor of Gypsum - Stawski, T.M.; Van Driessche, A.E.S.; Besselink, R.; Byrne, Emily; Raiteri, Paolo; Gale, Julian; Benning, L.G. (AMER CHEMICAL SOC, 2019)
© 2019 American Chemical Society. Understanding the gypsum (CaSO4·2H2O) formation pathway from aqueous solution has been the subject of intensive research in the past years. This interest stems from the fact that gypsum appears to fall into a broader category of crystalline materials whose formation does not follow classical nucleation and growth theories. The pathways involve transitory precursor cluster species, yet the actual structural properties of such clusters are not very well understood. Here, we show how in situ high-energy X-ray diffraction experiments and molecular dynamics (MD) simulations can be combined to derive the structure of small CaSO4 clusters, which are precursors of crystalline gypsum. We fitted several plausible structures to the derived pair distribution functions and explored their dynamic properties using unbiased MD simulations based on both rigid ion and polarizable force fields. Determination of the structure and (meta)stability of the primary species is important from both a fundamental and applied perspective; for example, this will allow for an improved design of additives for greater control of the nucleation pathway.